2021
DOI: 10.1001/jamanetworkopen.2021.19151
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Antiviral Agents for Seasonal Influenza Outcomes in Healthy Adults and Children

Abstract: Key Points Question What antiviral agents for treating seasonal influenza are associated with the most safety and best outcomes among healthy adults and children? Findings This network meta-analysis of 26 randomized clinical trials, including 11 897 patients, found that antiviral agents were associated with significantly greater efficacy than placebo in shortening the duration of influenza symptoms; zanamivir was associated with the shortest time to allevia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 78 publications
2
27
0
1
Order By: Relevance
“…Moreover, it is also recommended that this high-risk group be treated with Oseltamivir or Zanamivir as soon as possible whenever they have uncomplicated illness due to confirmed or strongly suspected with virus infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is also recommended that this high-risk group be treated with Oseltamivir or Zanamivir as soon as possible whenever they have uncomplicated illness due to confirmed or strongly suspected with virus infection [27].…”
Section: Discussionmentioning
confidence: 99%
“…Neben Oseltamivir stehen die weiteren Neuraminidase-Inhibitoren Peramivir und Zanamivir, sowie der Endonuklease-Inhibitor Baloxavir marboxil zu Verfügung. Eine kürzlich veröffentlichte Metaanalyse wertete 26 randomisiert kontrollierte Studien mit insgesamt 11 897 Patient*innen aus, welche die antiviralen Substanzen gegeneinander oder gegen Placebo verglichen haben 27 . Alle untersuchten Substanzen gingen mit einer Verkürzung der Zeit bis zur Symptombesserung einher.…”
Section: Therapieunclassified
“…A recent clinical trial in Japan in children between 6 and 12 concluded that BXM was efficacious and safe for Japanese patients with influenza infection [24]. A comparison of the antiviral medicines in Japan showed that BXM reduced the rates of complications in patients suffering from flu [25]. The main concern remains the development of resistance, for which insufficient data are available for the moment.…”
Section: Medical Interestmentioning
confidence: 99%